Perform the following subtraction between bases: 35

We do this by converting both terms to base 10

Convert 35

Move left to right starting with a power of 1 and decrease powers by 1 until we get to the last term

Since term 1 is 3, we assign it a value of 3 * (6

Our total sum is now equal to: 0 + 18 = 18.

Since term 2 is 5, we assign it a value of 5 * (6

Our total sum is now equal to: 18 + 5 = 23.

We've evaluated all 2 terms and arrived at our answer:

Expressing in expansion, we get: 3(6

Simplifying the expansion, we get: 18 + 5 =

Convert 42

Move left to right starting with a power of 1 and decrease powers by 1 until we get to the last term

Since term 1 is 4, we assign it a value of 4 * (8

Our total sum is now equal to: 0 + 32 = 32.

Since term 2 is 2, we assign it a value of 2 * (8

Our total sum is now equal to: 32 + 2 = 34.

We've evaluated all 2 terms and arrived at our answer:

Expressing in expansion, we get: 4(8

Simplifying the expansion, we get: 32 + 2 =

23 - 34 =